Mujeres en el ballet: maestras, bailarinas y productoras en Guadalajara - Cristina Castellano (Les Cahiers ALHIM)
The history of classical dance in Latin America is linked to the colonial history of the continent and to its emancipation movements. Schools, academies and ballet companies emerged in the cities of these countries with many peripheral regions and municipalities being left out. The aim of this study is to show the dynamics of local producers resisting the arrival of numerous imported shows that are highly and methodically produced then plopped down in the middle of their city. It uses, as a case study, the participation of producers, teachers and dancers from Guadalajara (Mexico) who made an ambitious ensamble of Swan Lake in a natural space. The production of a show between 1999 and 2004 is analyzed here, to reveal the absence of support from local government cultural institutions and the existence of social actoresses who with astuteness, intervened in helpless settings of programming that lacked artistic development and promotion. The complexity of staging a dance performance is discussed here and debated with theses which corporeity and ethnicity are the central axis of the dance and gender discourse.